A prospective study of ocular involvement secondary to ear, nose and throat disorders in a tertiary care centre, Telangana - ., Novshaba; Bhushan, Ivaturi Phani; Reddy, L. Sudarshan; Divya, Jaina (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Eye lies in close anatomical relation to ear, nose and throat due to which it is liable to get involved secondary to ENT disorders. Hence ENT disorders can manifest with varied ocular symptoms due to involvement of orbit and its content. Early diagnosis and treatment helps in reducing the mortality associated with it. Methods: All age group of patients presenting with ocular symptoms secondary to ENT disorders were reported accounting to 171 cases during 2 years of duration (June 2017-June 2019). Data regarding age, gender, clinical profile, etiology and management were collected and statistical analysis was done. Results: The maximum incidence was in young and middle aged group of patients. Males were most commonly affected. The majority of them were Infective or granulomatous (59, 34%) followed by traumatic (45, 26%) and neoplastic (44, 26%). The most common ocular involvement was proptosis (53) and the most common etiology was neoplastic (32 neoplastic cases caused proptosis) of which sinonasal squamous cell carcinoma (SCC) (8) followed by juvenile nasopharyngeal angiofibroma (JNA) (7) were the most common neoplastic cause for proptosis. Conclusions: Early recognition and management can pave the path to prevention of mortality and morbidity associated with ocular involvement secondary to ear, nose, throat (ENT) disorders.